Effects of methylhesperidin on coronary, renal and cerebral circulation in dogs - Feng Ming-guo; Feng Gao-Hong; Zhou Qian-Gui (Acta Pharmacologica Sinica, 2016)
Methylhesperidin (MH) 40 mg/kg iv markedly reduced the vascular resistance of the coronary. internal carotid and renal arteries in anesthetized dogs. MH significantly increased the blood flows of these arteries. The fall in arterial blood pressure and the volume increment were measured by an electromagnetic flowmeter. Tetramethylpyrazine (TMP, ligustrazin) 4 mg/kg iv produced a significant increase in the coronary and cerebral blood flows and a striking reduction in vascular resistance.